If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3y+25=2y+36
We move all terms to the left:
3y+25-(2y+36)=0
We get rid of parentheses
3y-2y-36+25=0
We add all the numbers together, and all the variables
y-11=0
We move all terms containing y to the left, all other terms to the right
y=11
| 8(x+12)=92 | | X2-56x+768=0 | | x+4=5x-12 | | x+1,6=4,2 | | 3(x5)+1=2+x | | 2(6x+2)=40 | | 2y-5=4y+7 | | –10s+6=–10s | | -16y-19=-15y | | 5.87x+3.11x-2=10 | | 3x-(2x-7x)=9 | | 2-3=7x-18 | | 5x+4×x-2×3x+7=180 | | 9n-5=7n+7 | | -7x+10+6x=20 | | 5(4x-10)=50 | | -2=3x^2+x-5 | | -7n=343 | | 2-3x=7x-18 | | -20q-19=20+15-17q | | n4+3=9 | | 15x^2+2.4x-0.64=0 | | k/3+15=22 | | −75=−15b | | -28=3.5m | | -=3x^2+x-5 | | 40(0.25-t)=70t | | m/5+7=15 | | 10+6h=4h | | 2a-7=4a= | | 4+10+3u=-9u-10 | | (X-5)=12+2x |